Prediction of uranium concentration profiles along a continuous extraction column (Chemical Engineering Research Bulletin, 2015)
The increased growth in energy demand has a direct impact on the growing interest of uranium extraction. Phosphoric acid attracts a great attention because of its uranium content. The solvent extraction is the most widely used techniques for uranium separation from phosphoric acid. In the present work, the simulation of the uranium extraction along a continuous counter current column has been conducted. A computer code that accounts for mass balances and equilibrium data has been developed. The performed simulations allow to obtain the concentration profiles of uranium along the extraction column and led to assess the effect of operating conditions on the extraction performances. DOI: http://dx.doi.org/10.3329/cerb.v17i1.22916 Chemical Engineering Research Bulletin 17(2015) 34-39